Tc-99m-MAA lung shunt fraction before Y-90 radioembolization is low among patients with non-hepatocellular carcinoma malignancies. Issue 11 (November 2019) - Elsayed, Mohammad; Martin, Jonathan G.; Dabrowiecki, Alexander; Goldman, Daryl T.; Faraj, Razan; McMahon, James T.; Kokabi, Nima; Duszak, Richard; Newsome, Janice; Bercu, Zachary L.
Abstract : Objective: Lung shunt fraction studies using technetium-99 m macro aggregated albumin are routinely performed before yttrium-90 radioembolization regardless of underlying liver malignancy type. This study evaluates the role of lung shunt fraction studies in hepatocellular carcinoma compared to non-hepatocellular carcinoma liver tumors. Methods: A single-institution retrospective analysis of all pre-yttrium-90 technetium-99 m macro aggregated albumin lung shunt fraction studies between November 2012 to March 2018 was performed. Patient variables including age, underlying malignancy, laboratory values, lung shunt fraction, and severity of liver disease were compared between hepatocellular carcinoma and non-hepatocellular carcinoma cases. Results: A total of 734 technetium-99 m macro aggregated albumin studies were identified in 653 patients. Among these cases, the liver tumor was hepatocellular carcinoma in 368 (50.1%), colorectal cancer in 112 (15.3%), neuroendocrine tumor in 89 (12.1%), cholangiocarcinoma in 59 (8.0%), breast cancer in 27 (3.7%), and other metastatic malignancies in 79 (10.7%). The mean lung shunt fraction for non-hepatocellular carcinoma cases was 7.4%, which was significantly lower than the mean lung shunt fraction, 11.7%, for hepatocellular carcinoma cases ( P = 0.0001). In only one non-hepatocellular carcinoma case was yttrium-90 radioembolization not pursued due to high lung shunt fraction (69.3%), wherein large scale shunting was grossly apparent on angiography in a patient with metastatic gastrointestinal stromal tumor. In comparison, the lung shunt fraction was too high to pursue radioembolization in 37 hepatocellular carcinoma cases (mean lung shunt fraction 35.1%). Conclusion: Lung shunt fraction appears low among patients with non-hepatocellular carcinoma liver malignancies. Further analysis examining the necessity of pre-Y90 technetium-99 m macro aggregated albumin lung shunt fraction studies in patients with non-hepatocellular carcinoma malignancies is warranted, since a consolidated yttrium-90 radioembolization without prior lung shunt fraction evaluation could reduce resource consumption, improve workflows, and patient access.